The princess and the potty - Lewison, Wendy Cheyette (New york : Aladdin paperbacks, 1994)
When everything fails to persuade the princess to use her potty, the king and queen consult the royal advisor who gives them valuable advice
Keywords: Toilet training - fiction; Princess - fiction